Potential Use of Some Edible Fruits from Woody Plants: Their Antioxidant Properties and Changes in Phenolics during In Vitro Digestion - Gulay Ozkan; Ceren Karahan; Gulefsan Kapucu; Bayram Yurt; Esra Capanoglu (World Journal of Traditional Chinese Medicine, 2025)
Objective: In this study, five woody plants including Cotoneaster horizontalis (rockspray cotoneaster), Cotoneaster franchetii (orange cotoneaster), Elaeagnus angustifolia (Oleaster), Berberis thunbergii (Japanese barberry), and Malus floribunda (Japanese crabapple) were used for infusion preparation. Materials and Methods: The antioxidant potential and bioaccessibility of phenolics in the infusion were investigated before and after the simulation of in vitro gastrointestinal digestion. Results: Accordingly, the infusion of B. thunbergii (Japanese barberry) exhibited the highest antioxidant capacity (6418 ± 479 mg Trolox equivalents [TE]/100 g dry weight [dw]), as measured by CUPRAC assay, and the highest total phenolic content (689 ± 30 mg gallic acid equivalents/100 g dw). On the other side, the infusion of C. horizontalis (rockspray cotoneaster) had the greatest antioxidant capacity values determined by 1,1-diphenyl-2-picrylhydrazyl radical scavenging ability (2420 ± 132 mg TE/100 g dw). The stability of phenolics in infusions was found to vary from gastric to intestinal digestion passage. Conclusion: With their high antioxidant potential, it is clear from the results that these plants can be considered a good alternative with functional properties.